Adapting Small-Scale Fiber Production to the 21st Century: Maine’s Evolving Strategies - Welcomer, Stephanie; Reynolds, Mikayla (Maine Policy Review, 2024)
This study, funded by the US Small Business Administration, aims to better understand the operational, strategic, and economic dimensions of Maine’s fiber producers’ businesses. Fiber producers are those raising animal-based fiber, including sheep, alpacas, rabbits, and goats. The producer focus of this paper highlights the responses from 27 fiber producers and their insights into the realities of Maine’s fiber sector.